Counseling on Transformer Learning Activities at SMK Kartika XIX Bandung - Jambola, Lucia; Darlis, Arsyad Ramadhan; Lidyawati, Lita; Fauziah, Dini; Susana, Ratna (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
Comprehending transformers is essential due to their critical function in contemporary electrical systems, including power distribution, battery charging, and diverse technological applications. This counseling aimed to enhance the educational program and deepen the understanding of SMK Kartika XIX-1 Bandung students concerning the operational principles of transformers. The employed approaches encompass the provision of resources, demonstrations, simulations, and evaluations. The results indicated that prior to the counseling, 100% of students had not participated in a transformer simulation. Following the simulation, 50% of students comprehended the concept of a transformer. This coaching is for students to comprehend the fundamental theory of transformers and to apply this information practically, so enhancing their readiness to confront workplace challenges.